Flight test of a pseudo‐ranging signal compatible with existing distance measuring equipment (DME) ground stations. Issue 3 (29th July 2020) - Lo, Sherman; Chen, Yu‐Hsuan; Enge, Per; Pelgrum, Wouter; Li, Kuangmin; Weida, George; Soelter, Achim
Abstract: Distance measuring equipment (DME) has been a cornerstone of aviation navigation for the last 70 years. While GNSS is taking an increasingly important role in civil aviation, DME can still play an important role in a robust aviation infrastructure in the foreseeable future. Advanced concepts have been developed to improve DME performance and capabilities. One concept is a DME‐based pseudolite that position modulates existing DME pulse pairs. It is interoperable with DME operations and can be generated using the currently fielded DME transponders with an appliqué. This concept is suitable as a robust alternative to GNSS for aviation navigation or timing. The paper examines the performance of DME pseudolite implemented via an appliqué on a DME transponder. The paper examines the synchronization and data performance of the DME pseudolite signal in the air and on the ground. The paper compares the actual performance to theoretical results.